Role of Ferredoxin and Flavodoxins in Bacillus subtilis Fatty Acid Desaturation - Chazarreta-Cifre, Lorena (American Society for Microbiology, 2011)
The Bacillus subtilis acyl lipid desaturase (Δ5-Des) is an iron-dependent integral membrane protein able to selectively introduce double bonds into long-chain fatty acids. In the last decade since its discovery, the molecular mechanism of Δ5-Des expression has been studied extensively. However, the mechanism of desaturation, which must rely on unknown bacterial proteins for electron transfer, has not yet been explored. The B. subtilis genome encodes three proteins that can act as potential electron donors of Δ5-Des, ferredoxin (Fer) and two flavodoxins (Flds) (YkuN and YkuP), which are encoded by the ykuNOP operon. Here we report that the disruption of either the fer gene or the ykuNOP operon decreases the desaturation of palmitic acid by ∼30%. Nevertheless, a fer ykuNOP mutant abolished the desaturation reaction almost completely. Our results establish Fer and the two Flds as redox partners for Δ5-Des and suggest that the Fer and Fld proteins could function physiologically in the biosynthesis of unsaturated fatty acids in B. subtilis. Although Flds have extensively been described as partners in a number of redox processes, this is the first report describing their role as electron donors in the fatty acid desaturation reaction.